Cell-free Fetal DNA Analysis in Maternal Plasma as Screening Test for Trisomies 21, 18, and 13 in Twin Pregnancy. Issue 2 (February 2019) - Le Conte, G.; Letourneau, A.; Jani, J.; Kleinfinger, P.; Lohmann, L.; Costa, J.-M.; Benachi, A.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2018;52(3):318–324) Increased use of fertility treatment and advanced maternal age contribute to the increased prevalence of twin pregnancy, which is currently approximately 3% in the United States. Screening for trisomy 21 in twins largely relies on maternal age and nuchal translucency measurement in the first trimester, as well as first- and second-trimester serum screening.